Hepatoid adenocarcinoma of the duodenal papilla with hepatic metastases: A case report and literature review - Han, Lu; Ding, Naiqing; Li, Li; Wei, Xiao; Hu, Jing; Liu, Baorui; Qian, Xiaoping (Frontiers in Oncology, 2022)
Hepatoid adenocarcinoma of the duodenum is a rare special type of adenocarcinoma, featured by hepatocyte components in primary adenocarcinoma of the duodenum. It has the characteristics of high malignancy, invasiveness, rapid progress, and poor prognosis. An abnormal elevation of serum alpha-fetoprotein (AFP) may occur in most cases. The diagnosis is mainly based on pathological morphology. Here, we reported a case of hepatic adenocarcinoma of the duodenum. The middle-aged female patient had an ampulla mass at diagnosis and received radical pancreaticoduodenectomy. The postoperative pathology was stage IIIA duodenal adenocarcinoma. At 1 month after surgery, she had multiple intrahepatic metastases and retroperitoneal lymph node metastasis; the AFP level was 300 ng/ml at that time. As she refused target therapy, two cycles of capecitabine-oxaliplatin (XELOX) chemotherapy were performed. However, the AFP elevated from 300 to 1,931.90 ng/ml, and the disease progressed rapidly. Immunohistochemistry (IHC) of tissue samples from presurgical endoscopic ultrasound guided fine needle aspiration (EUS-FNA), surgery, and liver biopsy showed positive AFP staining. Combining the abnormal elevation of serum AFP and microscopic pathological morphology, this case is diagnosed as hepatoid adenocarcinoma of the duodenum with liver metastasis. The physical condition of this patient was too poor to receive follow-up treatment. She died of the rapid disease progression with an overall survival time of 161 days. Considering that in most patients with hepatoid adenocarcinoma the abnormal elevation of serum AFP occurs preoperatively and returns to normal postoperatively rather than normal before surgery and increased after surgery, the primary lesion is located in the stomach rather than the intestine, and the patients are more often older men rather than middle-aged women; this case is rare particularly. Therefore, reporting this case with complete case data may be helpful to further study, so as to improve the understanding of this special type of malignant tumor.